Intensity‐modulated radiotherapy using simultaneous‐integrated boost for definitive treatment of locally advanced mucosal head and neck cancer: Outcomes from a single‐institution series. Issue 3 (17th January 2013) - Johnston, Meredith; Guo, Linxin; Back, Michael; Guminski, Alex; Lee, Adrian; Hanna, Catherine; Veivers, David; Wignall, Andrew; Eade, Thomas
Abstract Introduction The study aims to report outcomes for patients treated using intensity‐modulated radiotherapy (IMRT) with simultaneous‐integrated boost and weekly cisplatin for American Joint Committee on Cancer stage III/IV mucosal head and neck squamous cell carcinomas (HNSCCs). Methods Records for 67 patients treated definitively with IMRT for HNSCC were reviewed. By including only those treated with weekly cisplatin, 45 patients were eligible for analysis. Treatment outcomes, effect of patient, tumour and treatment characteristics on disease recurrence were analysed. Results All patients completed IMRT to 7000 cGy in 35 fractions, with concurrent weekly cisplatin 40 mg/m2 (median 6 cycles). Median follow‐up was 28 months for living patients. Two‐year loco‐regional recurrence‐free, metastasis‐free and overall survival were 85.4, 81.0 and 87.4%, respectively. Local recurrence occurred in three patients, and distant recurrence in eight patients. Conclusions Our results show efficacy of IMRT and weekly cisplatin in the treatment of stage III/IV HNSCC at our institution with respect to loco‐regional control.